Analysis of microglial BDNF function and expression in the motor cortex - Honey, Diana; Wosnitzka, Erin; Klann, Eric; Weinhard, Laetitia (Frontiers in Cellular Neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF) is a neurotrophin that regulates several aspects of brain function. Although numerous studies have demonstrated the expression and function of BDNF in neurons, its expression in microglia remains controversial. Using a combination of genetic tools and fluorescence imaging, we analyzed BDNF expression pattern and investigated the effect of microglial BDNF deletion on neuronal activity, early-stage spine formation, and microglia-neuron interactions in the motor cortex. Our results suggest that microglia do not express BDNF in sufficient amounts to modulate neuronal function.